Pengaruh Kepemimpinan Transformasional dan Employee Engagement terhadap Kepuasan Kerja Karyawan Rumah Sakit Permata Kuningan dengan Relasi Sosial sebagai Variabel Moderasi - Demi Paranita Rustandi; Lili Karmela Fitriani (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The purpose of this study was to analyze the extent to which Transformational Leadership and Employee Engagement affect Employee Job Satisfaction at Permata Kuningan Hospital with Social Relation as a Moderating Variable. This research used a survey method, with a quantitative descriptive analysis approach. The variables in this study are Transformational Leadership and Employee Engagement (X), and job satisfaction (Y) as the dependent variable. The population that will be used as research is Permata Kuningan Employee, namely 120 people. Data were analyzed with Moderated Regression Analysis using SPSS 22.0 for Windows.Based on the results of data analysis, it was found that the Fcount value is greater than Ftable with a significance value of less than 0.05, this means that Transformational Leadership and Employee Engagement both affect Job Satisfaction, meaning that anychange in Job Satisfaction simultaneously strengthens and will lead to changes in Job Satisfaction